Shape Effect Analysis of the Mechanical Properties of PVC-Coated Fabrics under Off-Axis Tension - Lanlan Zhang; Yingying Zhang; Qichong Zhao; Junhao Xu; Jigang Xue (Advances in Materials Science and Engineering)
This paper selects polyvinyl chloride- (PVC-) coated fabrics to study its off-axial tensile behaviors under different off-axis angles including 0°, 15°, 30°, 45°, 60°, 75°, and 90°. In the experiment, dumbbell-shaped and strip-shaped specimens are analyzed for shape effect. The variations in the strain distribution are studied by using digital image correlation (DIC) noncontact full-field measurement system. The shape and off-axis angle of specimens are analyzed to predict the influences of shape effect. The results show that the longitudinal strain and shear strain of the coated fabrics are obviously symmetrical to the off-axis direction. The shear strain distribution of the two kinds is basically the same, but the longitudinal strain fields are different. The off-axis tensile properties of the material are obviously anisotropic and nonlinear. The tensile testing curve of the specimens mainly consists of three stages: initial linear stage, deformation strengthening stage, and stress strengthening stage. At 0°, the tensile strength is the largest and the elongation at break is the smallest. In contrast, at 45°, the elongation at break is the highest and the tensile strength was the smallest. The properties under the other off-axis angles were between these two extremes.